LEARNING ANGKLUNG AT SAUNG UDJO: THE EXPERIENCE OF STUDENTS OF THE P MM 3 PROGRAM AT THE INDONESIAN EDUCATION UNIVERSITY IN UNDERSTANDING AND PLAYING ANGKLUNG - Yuli Musfiani; Cheriani; Jusman (PT. Jurnal Center Indonesia Publisher, 2025)
This article presents the experiences of students from the Independent Student Exchange Program (PMM) 3 at the Indonesian Education University in understanding and playing angklung at Saung Angklung Udjo. From the results of the interviews conducted, it was revealed that before participating in this activity, most students had never tried playing angklung. However, after participating in the angklung learning activity at Saung Angklung Udjo, a significant increase in their skills was seen. In addition, students also showed an increase in understanding of the cultural values of angklung as a traditional musical instrument. Several factors that contributed to the success of this learning included the quality of teaching, adequate facilities, time and intensity of practice, and student motivation and interest. The positive experiences gained during learning at Saung Angklung Udjo not only improved technical skills, but also instilled cultural values and togetherness among students. This research is expected to provide valuable insights for the development of arts and culture education curriculum in Indonesia.